Imaging diagnosis: ultrasonographic appearance of small bowel metastasis from canine mammary carcinoma - Domínguez, Elisabet; Anadón, Eduard; Espada, Yvonne; Grau-Roma, Llorenc; Majó, Natàlia; Novellas, Rosa (Wiley, 2013)
A 10-year-old entire female Beagle dog was evaluated for an acute history of lethargy, anorexia, and diarrhea. Mammary tumors were detected during physical examination. Ultrasonographic scanning revealed the presence of a unique pattern of multiple, well-defined and well-marginated hypoechoic nodules in the muscularis layer of the jejunum. These nodules were not associated with changes in the rest of the normal intestinal layering and were not causing signs of intestinal obstruction. Mammary carcinoma metastases to the intestinal muscularis layer were diagnosed based on histopathological examination.